Digital Business Transformation and Its Impact on Organizational Performance in the Banking Industry: The Mediating Role of Digital Capability and Employee Adaptability - Ayi Wahid; Hery Wihasnanto; Rosna Yuherlina Siahaan; Rini Martiwi; Ari Wijaya (Greenation International Journal of Economics and Accounting, 2026)
Advances in digital technology are driving the banking industry to undertake business transformation to improve organizational performance. This study aims to analyze the influence of digital business transformation on organizational performance, with digital capabilities and employee adaptability as mediating variables. The study used a quantitative approach through a survey of banking employees involved in digital transformation. Data were analyzed using Structural Equation Modeling (SEM). The results show that digital business transformation has a positive and significant impact on organizational performance, as well as improving employee digital capabilities and adaptability. Both variables also positively influence organizational performance and act as partial mediators in the relationship between digital business transformation and organizational performance. These findings indicate that the success of digital transformation depends not only on technology investment but also on strengthening employee digital capabilities and adaptability. This study provides an empirical contribution to the development of digital transformation studies in the banking sector and provides input for bank management in improving organizational performance sustainably.